Miracles revisited : New Testament miracle stories and their concepts of reality - Alkier, Stefan; Weissenrieder, Annette, 1967- (Studies of the Bible and its reception, 2013)
The book revisits New Testament and other miracle stories with regard to three dimensions: 1. It proposes to connect the interpretation of miracle stories to concepts of reality. 2. It emphasizes the political implications of miracle stories and their interpretations. 3. It demands to read miracle stories within its contexts. The book addresses how ancient concepts of reality, always complex, come to expression in stories of miraculous healings and their reception in medicine, art, literature, theology and philosophy, from classic antiquity to the Middle Ages.